A socio-technical systems framework for risk management in financial services: Some empirical evidence from a case study of the Irish Banking Crisis. Issue 25 (2019) - Organ, John; Stapleton, Larry
Abstract: This paper describes a framework which addresses predominant failure to incorporate human factors in systemic financial systems. This framework recognizes the additional human factors brought to an already complicated financial technological environment. The contribution of this paper is to set out a framework which can be used to inform policy and reframe risk management in Irish banking more generally. Its shows how society at large can draw formal, scientifically reliable and rich insights from costly public inquiries to learn lessons from catastrophic failures such as the banking crisis of 2008-2009.